2010
DOI: 10.1007/s00011-010-0299-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of two different dosing regimens of terlipressin on organ functions in ovine endotoxemia

Abstract: Continuous infusion of low-dose terlipressin preserved several surrogate parameters of organ function better than intermittent bolus injections in sheep with systemic inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 34 publications
0
15
1
1
Order By: Relevance
“…Sheep have been used widely to study a variety of disorders related to human disease (Petersson et al , 2002; Petersson et al , 2004; Soehnlein et al , 2010), including inflammatory conditions in both adult and fetal sheep (Hagberg et al , 2002; Mallard et al , 2003; Collins et al , 2010; Hillman et al , 2010; Lange et al , 2010; Shah et al , 2010; Soehnlein et al , 2010; Rehberg et al , 2011). Monoclonal antibodies (mAbs) specific for ovine IL-1 β and IL-6 have been generated (Rothel et al , 1997; McWaters et al , 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Sheep have been used widely to study a variety of disorders related to human disease (Petersson et al , 2002; Petersson et al , 2004; Soehnlein et al , 2010), including inflammatory conditions in both adult and fetal sheep (Hagberg et al , 2002; Mallard et al , 2003; Collins et al , 2010; Hillman et al , 2010; Lange et al , 2010; Shah et al , 2010; Soehnlein et al , 2010; Rehberg et al , 2011). Monoclonal antibodies (mAbs) specific for ovine IL-1 β and IL-6 have been generated (Rothel et al , 1997; McWaters et al , 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Other notable changes include improved gas exchange, decreased levels of myeloperoxidase (MPO) and lung 3-nitrotyrosine (65). There was also an overall improvement in pulmonary function suggesting that blocking nitric oxide-peroxynitrite pathway may ameliorate some effects of septic shock (65).The ovine model of sepsis and septic shock has made important contributions in the areas of cardiovascular (66) and pulmonary research as well as in determining the efficacy of fluids (58) and therapeutic agents (67), such as anticoagulants (68) and recombinant human protein C (69) to improve sepsis outcomes.…”
Section: Ovine Models Of Sepsismentioning
confidence: 99%
“…(8)(9)(10) Vasopressin is a potent vasopressor with extended purposes in the treatment of severe trauma, septic shock, cardiac diseases and during cardiopulmonary resuscitation. (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) In addition, a few researchers have found that vasopressin is absorbed well via the mucosa of the airway and alveoli. (23)(24)(25) The combination of a LMA and vasopressin could be a practical management tool in pre-hospital settings.…”
Section: Introductionmentioning
confidence: 99%